The Presence of Ribulose 1,5-Diphosphate Carboxylase in the Nonphotosynthetic Endosperm of Germinating Castor Beans - Benedict, C. R. (1973)
Ribulose 1,5-diphosphate carboxylase was detected in extracts of germinating castor bean (Ricinus communis var. Hale) endosperms. This is the first report of this enzyme in a nonphotosynthetic (no chlorophyll) plant tissue. Radioactive 3-phosphoglyceric acid has been identified as the principle product resulting from the enzymatic condensation of (14)C-bicarbonate and ribulose-1,5-diP in endosperm extracts. The Km values of bicarbonate and ribulose-1,5-diP for the endosperm carboxylase are 1.14 × 10(−2)m and 7.5 × 10(−5)m, respectively. The carboxylase activity peaks at 4 days in endosperms of castor beans germinated in the dark. The specific activity of the carboxylase at this stage of germination is 4.3 μmoles of 3-phosphoglycerate formed/mg protein·hr. The presence of ribulose-1,5-diP carboxylase and other enzymes of the reductive pentose phosphate pathway show the potential of this pathway in castor bean endosperms.